2019
DOI: 10.1017/s1355617719000961
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Premorbid Adjustment and Autistic Traits on Social Cognitive Dysfunction in Schizophrenia

Abstract: Objectives:Premorbid dysfunction during childhood and adolescence is well documented in patients with schizophrenia. Literature pointed out multiple premorbid trajectories leading to different patients’ cognitive status, symptomatology, and global functioning after disease onset. This study aimed at identifying groups of premorbid trajectories and disentangling between group differences in clinical and cognitive measures, focusing on theory of mind (ToM) and autistic traits (ATs).Methods:Ninety-seven patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…Relative to the second aim, we tested the effects of cognitive abilities, sequentially mediated by sociocognitive and pragmatic skills, on different domains of functioning. In line with a large body of literature highlighting the heterogeneity that characterizes neuropsychological predictors of functioning in schizophrenia (Bambini et al, 2016; Bechi et al, 2018; Bechi, Agostoni, Buonocore, Bosinelli, et al, 2020; Bechi, Spangaro, Agostoni, et al, 2019; Vaskinn et al, 2014), we expected different functional domains to be associated with specific neuropsychological predictors.…”
mentioning
confidence: 84%
“…Relative to the second aim, we tested the effects of cognitive abilities, sequentially mediated by sociocognitive and pragmatic skills, on different domains of functioning. In line with a large body of literature highlighting the heterogeneity that characterizes neuropsychological predictors of functioning in schizophrenia (Bambini et al, 2016; Bechi et al, 2018; Bechi, Agostoni, Buonocore, Bosinelli, et al, 2020; Bechi, Spangaro, Agostoni, et al, 2019; Vaskinn et al, 2014), we expected different functional domains to be associated with specific neuropsychological predictors.…”
mentioning
confidence: 84%
“…Second, cognitive abilities, and especially attention and executive functions (Kurtz et al, 2016), and sociocognitive skills, and especially Theory of Mind and empathic abilities (Mucci et al, 2021), are considered major predictors of daily functioning in patients with schizophrenia, accounting for 20-30% of the variance (Best et al, 2014). Third, and in light of accumulating evidence suggesting that autistic symptoms can co-occur in individuals with schizophrenia, a number of studies have shown that co-occurring autistic symptoms in schizophrenia are significantly associated with lower quality of life and functioning (Bechi et al, 2019(Bechi et al, , 2020b, although this seems to be specific to symptomatically severe patients (Bechi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This appears particularly relevant in light of the chronic course of the disease, in which over time there is a greater prevalence of both Mets and FM, as a consequence of the physiological increase in age-related risk as well as of the increased risk related specifically to the disease (i.e., lifestyle, pharmacological treatment). Therefore, FM, as well as MetS, may represent a factor that can help explain the heterogeneity of the longitudinal trajectories of cognitive deficit in schizophrenia ( Carruthers et al, 2019 ; Bechi et al, 2020 ; Spangaro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%